Microfiltración de bases cavitarias expuestas a peróxido de hidrogeno y peróxido de carbamida. - Vásquez Revelo, Evelyn Vanessa (2024)
External cervical resorption is a complication related to internal tooth whitening in non-vital teeth. Therefore, the level of microleakage generated by hydrogen peroxide and carbamide peroxide when in contact with intraoral filling materials was investigated using an in vitro study, methylene blue staining technique, and observation by stereoscopic microscopy. Sixty ivorine lateral incisors were selected by non-probabilistic sampling by convenience; they were endodontized and obturated with the lateral condensation technique, and the cavity bases were placed with 3 mm of a thickness (Glass Ionomer=20, Biodentine=20, Biodentine=20, Resin=20), the specimens were stored in distilled water in an oven at 37º for three days for stabilization, then the Walking Bleach technique was applied with Hydrogen Peroxide at 35% and Carbamide Peroxide at 37%, they were stored and after 24 hours the first 30 samples were analyzed, repeated for the 30 samples of day 4. The statistical analysis detected a higher mean microfiltration for Biodentine with 93.16 um, followed by Glass Ionomer with 79.18 um, and Fluid Resin with 52.72 um, being of greater length for those exposed to Hydrogen Peroxide; the temporality was an influential factor since on day four the microfiltration could be elevated. To conclude, all the materials suffered microleakage after bleaching, but not the control group, except for one sample of Glass Ionomer.